Bronquiolitos aguda del lactante por virus sincicial respiratorio. Estudio de 258 casos. - Gutiérrez Muñiz, José A.; Guzmán Rodríguez, Enrique; Cabezas Cabezas, Jorge; Más Lago, Pedro; Goyenechea Hernández, Ángel; Moluk, Eugenio (Revista Cubana de Pediatría, 2023)
Análisis de 258 casos.